Exchange rate volatility and private consumption in Sub-Saharan African countries: A system-GMM dynamic panel analysis - Isiaq Olasunkanmi Oseni (Future Business Journal, 2016)
The insurgence of exchange rate volatility over the years has gained the attention of not only the scholars but also the policy makers around the world. Also, its effects on private consumption are a missing gap in the literature most especially in Sub-Saharan African (SSA) Countries. Although, several studies have discussed the consequences of exchange rate volatility to growth but there is no documented empirical evidence on the relationship between exchange rate volatility and private consumption. This paper examines the effect of exchange rate volatility on private consumption in SSA countries using system-GMM dynamic panel and GARCH (1, 1) to generate exchange rate volatility series between 1999 and 2014. The exchange rate volatility series generated through GARCH (1, 1) fulfills the conditions of ARCH effect and volatility clustering. The result of the system-GMM shows that exchange rate volatility has negative and significant effect on private consumption in SSA countries. This result is further confirmed using various diagnostic tests such as Arellano and Bond test of first- and second-order serial correlation and Hansen J-statistic test of model specification and valid overidentified restrictions i.e. validity of instruments. Based on this, the study concludes that exchange rate volatility has significant negative effect on private consumption in SSA countries.
Keywords: 650; Dynamic panel; Exchange rate volatility; GARCH; Private consumption; System-GMM